CHARACTERIZATION OF TEMPERATURE AND RAINFALL AND THE CLIMATIC CLASSIFICATION TO TH STATE SLOPE OF THE ITARARA WATERSHED - Bodas Terassi, Paulo Miguel de [UNESP]; Garcia Tommaselli, Jose Tadeu [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2015)
This study aims to characterize the spatial and temporal variability of temperature and rainfall annual and seasonal, present the results obtained from the climatic water balance and determine the climatic types in the Parana State slope of the Itarare watershed. The rainfall data were obtained from thirteen rainfall gauges along the Parana Institute of Water and one weather station belonging to the Agronomic Institute of Parana. Were spatialized to temperature estimates provided by the University of Delaware (2014). Was used the climatic water balance of Thornthwaite and Mather (1955). Were applied the climate classification of Koppen (1948) and Thornthwaite (1948). The spatial distribution of isohyets showed that the southern sectors have the highest rainfall heights and showed a significant reduction for the eastern and northern sectors. The period of greatest concentration of rainfall occurs in the summer and spring. The biggest isotherms, the highest evapotranspiration values and lower water surplus values were identified for the northern sector. The use of climate classification system of Koppen (1948) made possible to delimit the study area into three climatic types: Cfb for the western and central sectors; Cfa for the northern sector; Cfa/Cfb for transient sectors. The methodology of Thornthwaite (1948) presented six climate types distinguishing the climatic characteristics of the river basin in accordance with the effective moisture content and thermal efficiency.
Keywords: rainfall; temperature; water availability; climate classification; watershed